Real-time detection of Seneca Valley virus by one-tube RPA-CRISPR/Cas12a assay - Ma, Lei; Zhu, Mengjie; Meng, Qingfeng; Wang, Yao; Wang, Xueping (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Senecavirus A (SVA) is a highly contagious virus that causes vesicular disease in pigs. At present, laboratory detection methods, such as virus isolation and polymerase chain reaction (PCR), required precision instruments and qualified personnel, making them unsuitable for point-of-care tests (POCT). Fortunately, the emergence of CRISPR/Cas system has provided new opportunities for fast and efficient pathogen detection. Methods This study successfully developed a precise and sensitive detection platform for diagnosing SVA by combining the CRISPR system with recombinase polymerase amplification (RPA). Results The minimum detection limit of the assay was 10 copies of the SVA genome. Meanwhile, the assay demonstrated high specificity. To validate the effectiveness of this system, we tested 85 swine clinical samples and found that the fluorescence method had a 100% coincidence rate compared to RT-qPCR. Discussion Overall, the RPA-CRISPR/Cas12a assay established in our study is a highly effective method for detecting SVA and holds great potential for practical applications in the resource-limited settings.